2020 한국인 영양소 섭취기준: 리보플라빈 - 이정은(Jung Eun Lee); 조진아(Jin Ah Cho); 김기남(Ki Nam Kim) (Journal of nutrition and health, 2022)
Riboflavin and its derivatives, flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD), are key components of mitochondrial energy metabolism and oxidation-reduction reactions. Proposed dietary reference intakes for Koreans (KDRIs), that is, estimated average requirements (EARs), for riboflavin, based on current knowledge of riboflavin and riboflavin derivative levels, and glutathione reductase activity, are 1.3 mg/d for men aged 19-64 years and 1.0 mg/d for women aged 19-64 years. By applying a coefficient of variance of 10%, reference nutrient intakes (RNIs) were set at 1.5 mg/d for men aged 19-64 years and 1.2 mg/d for women aged 19-64 years. Likewise, EARs and RNIs of riboflavin intake were proposed for all age groups and women in specific life stages such as pregnancy. Mean adult riboflavin intake for adults aged ≥ 19 years was 1.69 mg/d in Korea National Health and Nutrition Examination Survey (KNHANES) 2020, which was 124.9% of EAR according to the 2020 KDRIs. In the 2015-2017 KNHANES study, the mean riboflavin intake from foods and supplements was 2.79 mg/d for all age groups, and 32.7% of individuals consumed less riboflavin than EAR according to the 2020 KDRIs. For those that used supplements, mean intakes were 1.50 mg/d for riboflavin from foods, 10.26 mg/d from supplements, and 11.76 mg/d from food and supplements, and 5.5% of individuals consumed less riboflavin than EAR. Although the upper limit of riboflavin has not been established, the merits of increasing supplement use warrant further consideration. Also, additional epidemiologic and intervention studies are required to explore the role of riboflavin in the etiology of chronic diseases. 리보플라빈 (비타민 B2)은 한국인에게 섭취 부족의 우려가 있는 비타민으로서 에너지 대사를 포함한 산화/환원 반응의 조효소로서 작용한다. 적절한 섭취수준을 평가하는 방법으로는 적혈구에서의 리보플라빈 농도나 EGRAC, 혹은 소변의 리보플라빈 농도를 측정하는 것이다. 적혈구 리보플라빈 수준은 400 nmol/L (15 ㎍/100 mL) 이상을 적정수준, 270 nmol/L (10 ㎍/100 mL) 이하를 결핍으로 하거나 EGRAC 값이 1.2 이하인 경우 적정수준, 1.4이상이면 결핍으로 판정한다. 2020 한국인 영양소 섭취기준 개정 시 19-64세 성인의 2020 리보플라빈 평균필요량은 남자 1.3 mg/d, 여자 1.0 mg/d로 설정되었으며, 64-74세 남자 1.2 mg/d, 여자 0.9 mg/d, 75세 이상 남자 1.1 mg/d, 여자 0.8 mg/d로 성인 보다 낮게 설정되었다. 2020 국민건강영양조사 결과 19세 이상 우리나라 성인의 리보플라빈 평균 섭취량은 1.69 mg/d이며, 권장섭취량 대비 124.9% 였고, 보충제 섭취자들의 보충제로부터의 리보플라빈 섭취량은 평균 10.26 mg/d로 식품으로부터 섭취하는 1.50 mg에 비해 약 6.8배 높은 수준이었다 [18]. 2020 한국인 영양소 섭취기준에서 연령별, 성별 리보플라빈 권장섭취량은 각 생애주기 구간별 평균필요량에 변이계수 10%를 적용하여 평균필요량의 120% 수준으로 설정되었다 리보플라빈의 대표적 식품 급원으로는 유제품, 난류, 육류, 가금류와 생선류의 동물성 식품과 두류, 녹색채소류, 곡류 등이 있으며 2020 국민건강영양조사에 따르면 한국인의 리보플라빈 급원 식품으로 기여도가 높은 식품은 달걀, 라면, 돼지고기, 우유, 간장, 쇠고기, 배추김치, 닭고기, 고추가루, 시리얼 순이다. 최근 리보플라빈의 경우 비타민 보충제 외에도 다양한 건강기능성 식품섭취로 인해 보충제를 섭취하는 사람들의 경우 보충제로부터의 섭취수준이 식품으로부터의 섭취량을 훨씬 초과하고 있어 리보플라빈 영양상태 평가 시 보충제로부터 섭취하는 수준에 대한 평가가 향후 반드시 필요하다. 또한 2020 한국인 영양소 섭취기준 개정에서는 만성 질환 예방에 대한 부분은 아직 과학적 증거의 불충분으로 고려되지 않았으나 향후 만성질환과 관련된 역학연구 및 중재연구가 더 필요하다고 판단된다.